Debt management, dollarization and maturity structure of public securities: The experience of Bolivia - Walter Orellana; Esteban Vesperoni (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2007)
Public debt profiles have improved in Bolivia recently; in particular by extending the maturity structure and increasing the proportion of debt issued in domestic currency. This paper analyzes trends in public domestic debt in Bolivia since 2000, and the role of macroeconomic fundamentals and the debt management strategy adopted by the authorities. We analyze their role using transfer function models that suggest that both were critical in improving debt profiles, in particular the strengthening of the fiscal and international reserves positions, the recent appreciation of the Boliviano, and new prudential regulation that promotes the use of the latter. We also compare debt profiles with other countries in Latin America, and found that there is still room for improvement, both in terms of maturity structure and currency composition.
Keywords: E44; E52; G18; H63; 330; Bolivia; debt profiles; maturity structure; currency composition